2021
DOI: 10.1371/journal.pone.0257571
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular function and vasoactive peptides for early prediction of bronchopulmonary dysplasia

Abstract: Background To assess the prognostic value of early echocardiographic indices of right ventricular function and vasoactive peptides for prediction of bronchopulmonary dysplasia (BPD) or death in very preterm infants. Methods Prospective study involving 294 very preterm infants (median [IQR] gestational age 28.4 [26.4–30.4] weeks, birth weight 1065 [800–1380] g), of whom 57 developed BPD (oxygen supplementation at 36 weeks postmenstrual age) and 10 died. Tricuspid annular plane systolic excursion (TAPSE), righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…All studies were conducted in tertiary perinatal centres. Only four studies examined exclusively preterm infants born before 32 weeks of gestation ( 11 , 13 15 ) ( Table 1 ). The study by Helfer et al, 2014, included preterm infants born at 32 weeks gestation as the recruitment was per birth weight rather than gestational age ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were conducted in tertiary perinatal centres. Only four studies examined exclusively preterm infants born before 32 weeks of gestation ( 11 , 13 15 ) ( Table 1 ). The study by Helfer et al, 2014, included preterm infants born at 32 weeks gestation as the recruitment was per birth weight rather than gestational age ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies' timing and frequency of echo scans varied ( Table 2 ). Three studies performed one echo scan within the first two weeks after birth ( 13 , 15 , 17 ); one study had the echo scans performed on the first day after birth (DAB) ( 17 ), and the other two studies performed the echo scans at the 7th DAB, respectively ( 13 , 15 ). The remaining five studies had several echo scans performed within the first two weeks after birth ( 11 , 14 , 16 , 18 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, BPD-PH is associated with prolonged time on the respirator, longer oxygen dependency, higher tracheostomy rates, and higher frequency of readmissions to the intensive care setting compared to BPD alone [ 14 ]. Recently, it has been shown that echocardiographic right ventricular performance markers significantly worsen already on the 7th day of life (DOL) in very preterm infants who will later be diagnosed with BPD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%